2018
DOI: 10.1111/1744-7917.12603
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection of the secondary symbionts,Hamiltonella defensaandArsenophonussp. contribute to the performance of the major aphid pest,Aphis gossypii(Hemiptera: Aphididae)

Abstract: Bacterial endosymbionts play important roles in ecological traits of aphids. In this study, we characterize the bacterial endosymbionts of A. gossypii collected in Karaj, Iran and their role in the performance of the aphid. Our results indicated that beside Buchnera aphidicola, A. gossypii, also harbors both Hamiltonella defensa and Arsenophonus sp. Quantitative PCR (qPCR) results revealed that the populations of the endosymbionts increased throughout nymphal development up to adult emergence; thereafter, popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 68 publications
3
44
2
Order By: Relevance
“…Spiroplasma had extremely low relative abundance (< 0.005%) in two aphid samples, which may explain why it was not found before. The defensive symbiont Hamiltonella defensa was reported to infect all A. gossypii samples examined by Zhao et al [74], Ayoubi et al [77], and Zhang et al [76]. However, in our study, it was just carried by six samples at very low abundance (< 0.005%).…”
Section: Symbiont Diversity Of Aphis Gossypiicontrasting
confidence: 59%
See 2 more Smart Citations
“…Spiroplasma had extremely low relative abundance (< 0.005%) in two aphid samples, which may explain why it was not found before. The defensive symbiont Hamiltonella defensa was reported to infect all A. gossypii samples examined by Zhao et al [74], Ayoubi et al [77], and Zhang et al [76]. However, in our study, it was just carried by six samples at very low abundance (< 0.005%).…”
Section: Symbiont Diversity Of Aphis Gossypiicontrasting
confidence: 59%
“…Our data showed that Arsenophonus was the predominant facultative symbiont, with the highest infection prevalence and abundance. It has been reported in previous studies of A. gossypii [66,[73][74][75][76][77]. Jousselin et al [98] surveyed the distribution of Arsenophonus in aphids and revealed its high prevalence in the genus Aphis.…”
Section: Symbiont Diversity Of Aphis Gossypiimentioning
confidence: 79%
See 1 more Smart Citation
“…However, in A. gossypii, the presence of at least one facultative symbiont is almost systematic. H. defensa was recorded in A. spiraecola but not in A. gossypii even though previous studies have reported the presence of H. defensa in this aphid (Zhao et al, 2016;Ayoubi et al, 2020). We recorded similar percentage infections of A. gossypii and A. spiraecola with S. symbiotica and R. insecticola, but the percentage infection of these aphids with Arsenophonus differed.…”
Section: Discussioncontrasting
confidence: 49%
“…Bacteriophages required for protective symbiosis are recorded in various strains of this symbiont (Duron, 2014), but no defensive properties are reported for Aphis glycines infected with Arsenophonus (Wulff et al, 2013). Due to the high prevalence of Arsenophonus in populations of A. gossypii it is suggested that this facultative symbiont may be involved in host nutrition by mediating host plant range (Wagner et al, 2015;Zhao et al, 2016;Tian et al, 2019;Ayoubi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%